Music and conflict - O'Connell, John Morgan; Castelo-Branco, Salwa El-Shawan (University of Illinois Press, 2010)
"Until now, the intersection of music and conflict has been under-documented and under-theorized in ethnomusicology. Music and Conflict bravely addresses the 'darker side' of musical behavior, documenting how music sometimes works to incite violence and how it may also be used to rebuild communities torn apart by misunderstandings, conflict, and even war."--Nancy Guy, author of Peking Opera and Politics in Taiwan